On the establishment of two more alien mollusca (Chama aspersa Reeve, 1846 and Chama asperella Lamarck, 1819) in the eastern Mediterranean - OVALIS, P.; ZENETOS, A. (Mediterranean Marine Science, 2007)
The Indo-Pacific bivalvia Chama aspersa Reeve, 1846 and Chama asperella Lamarck, 1819 are recorded for the first time in Greek waters. These findings represent a considerable expansion in the eastern Mediterranean. Ship fouling is assumed as the most probable transportation means. However, natural dispersal via the Suez Canal is feasible as well.